Phát triển trí tuệ cảm xúc (EQ) cho trẻ mẫu giáo thông qua trò chơi học tập: Nghiên cứu tại một số trường mầm non trên địa bàn thành phố Hà Nội - Nguyễn, Thị Luyến; Đặng, Út Phượng (Tạp chí Giáo dục, 2025)
Emotional intelligence (EQ) is increasingly considered an important factor contributing to the formation of personality and social skills for children from the early stages of life. Choosing and organizing games to develop EQ for preschool children is attracting the attention of many preschool educators, which opens up many opportunities to contribute to improving the effectiveness of organizing educational activities for children, promoting the quality of education. The article systematizes the theory of EQ and learning games. Conducting a survey on the current awareness of preschool teachers on this issue, the results showed that teachers have positive awareness but lack effective implementation methods. On that basis, the article introduces some specific games to develop EQ components such as: emotional recognition, emotional expression, emotional regulation, empathy and cooperation in preschool children. Initially, research shows that developing EQ through learning games is a feasible direction, contributing to improving the quality of emotional education for children if applied properly and with professional support.